2007
DOI: 10.1242/jcs.010728
|View full text |Cite|
|
Sign up to set email alerts
|

The muscle-specific microRNAs miR-1 and miR-133 produce opposing effects on apoptosis by targeting HSP60, HSP70 and caspase-9 in cardiomyocytes

Abstract: The microRNAs miR-1 and miR-133 are preferentially expressed in cardiac and skeletal muscles and have been shown to regulate differentiation and proliferation of these cells. We report here a novel aspect of cellular function of miR-1 and miR-133 regulation of cardiomyocyte apoptosis. miR-1 and miR-133 produced opposing effects on apoptosis, induced by oxidative stress in H9c2 rat ventricular cells, with miR-1 being pro-apoptotic and miR-133 being anti-apoptotic. miR-1 level was significantly increased in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(182 citation statements)
references
References 30 publications
7
172
1
2
Order By: Relevance
“…This hypothesis would be in line with studies showing antiapoptotic effects of miR-133 [7,11,27]. As advanced heart failure in humans is associated with a reactivation of the fetal gene program as well as increased apoptosis [28,29], this is in agreement with our study showing higher miR-133 expression with low-grade heart failure.…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis would be in line with studies showing antiapoptotic effects of miR-133 [7,11,27]. As advanced heart failure in humans is associated with a reactivation of the fetal gene program as well as increased apoptosis [28,29], this is in agreement with our study showing higher miR-133 expression with low-grade heart failure.…”
Section: Discussionsupporting
confidence: 93%
“…However, considering the recent reports describing cell-to-cell transport of miRNAs [26] and of miRNAs as paracrine signaling molecules [27] one might speculate that the presence of miRNAs in circulation is not merely a by-product of myocardial necrosis but also implies a functional role for these molecules. miR-1 and miR-133a have been shown to regulate cardiomyocyte apoptosis through different mechanisms [28,29], whereas miR-208b and miR-499 have been shown to affect muscle function and performance by regulating myosin gene expression [30]. This might point towards a cardioprotective role for these miRNAs in the setting of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Using cell culture and animal model experiments, it has been recently shown that miR-1 and miR-133 have opposite roles in muscle development, with miR-1 promoting myoblast differentiation and miR-133 promoting myoblast proliferation [4] and apoptosis, with a proapoptotic role of miR-1 and antiapoptotic role of miR-133 [20]. It has been suggested that miR-1 and miR-133 also play an important role in determining cardiac automaticity in the developing heart, possibly by reexpression of the pacemaker channel genes HCN2 and HCN4 [21] .…”
Section: Discussionmentioning
confidence: 99%